Spotlight on Islam to the east of Bengal and particularly in the ages before judging the Islamic - Rafik, AB (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2669 IIUC STUDIES Vol. - 3, December 2006 (p 8-5)